DEVELOPING MATHEMATICS LEARNING MEDIA USING THE STEAM APPROACH : EFFORTS TO IMPROVE THE QUALITY OF DEEP LEARNING: Jawa Tengah, Indonesia - Aziz, Abdul; Iswahyudi Joko Suprayitno (Jurnal Math-UMB.EDU, 2025)
Development of mathematics learning media using the STEAM approach as a strategic effort in the process of adapting 21st century learning. The purpose of this study is to determine the process of developing mathematics learning media in an effort to improve the quality of deep learning. The research method used is the 4D development method consisting of Define, Design, Develop, and Disseminate. The subjects of this study were prospective mathematics teachers who were taking a mathematics animation multimedia course. In the define stage, prospective teachers analyzed materials that were considered difficult by students from teaching field practice or from previous learning experiences. Data containing materials that were difficult for students to learn were then analyzed to develop relevant media to reduce students' difficulties in understanding certain materials. Information collection related to student difficulties was obtained through the process of observation, direct interviews, and documentation of student learning outcomes to determine the causes of difficulties and from the difficult material identified for product design that could help students overcome their difficulties. The design was then followed up with the development of mathematical animation multimedia. In accessing mathematics learning so that it could be accessed by many parties, prospective teachers developed it in web form using Coding entered in Visual Studio Code which leads to HTML. The website containing mathematical animation multimedia was taught to teachers from Cambodia. Based on the animated multimedia created, Cambodian teachers gave positive appreciation and stated that the animated media created was appropriate. Keywords : Media, STEAM, Deep Learning